Using benchmarking for the primary allocation of EU allowances - an application to the German power sector - Joachim Schleich; Clemens Cremer (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2007)
Basing allocation of allowances for existing installations under the EU Emissions Trading Scheme on specific emission values (benchmarks) rather than on historic emissions may have several advantages. Benchmarking may recognize early action, provide higher incentives for replacing old installations and result in fewer distortions in case of updating, facilitate EU-wide harmonization of allocation rules or allow for simplified and more efficient closure rules. Applying an optimization model for the German power sector, we analyze the distributional effects of various allocation regimes across and within different generation technologies. Results illustrate that regimes with a single uniform benchmark for all fuels or with a single benchmark for coal- and lignite-fired plants imply substantial distributional effects. In particular, lignite- and old coal-fired plants would be made worse off. Under a regime with fuel-specific benchmarks for gas, coal, and lignite 50 % of the gas-fired plants and 4 % of the lignite and coal-fired plants would face an allowance deficit of at least 10 %, while primarily modern lignite-fired plants would benefit. Capping the surplus and shortage of allowances would further moderate the distributional effects, but may tarnish incentives for efficiency improvements and recognition of early action.
urn:nbn:de:0011-n-661589
Keywords: 330